A fuel cell powered autonomous surface vehicle: The Eco-SWAMP project. (17th June 2021) - Boscaino, V.; Odetti, A.; Marsala, G.; Di Cara, D.; Panzavecchia, N.; Caccia, M.; Tinè, G.
Abstract: Autonomous surface vehicles are becoming consolidated robotic tools for marine, coastal and inland surveys. Autonomous surface vehicles are usually equipped with electronic instruments to perform remotely controlled or autonomous geo-morphological, biological, chemical, physical analyses and data collection. Actually, well-established solutions provide battery power but the research focuses on introducing a fuel cell to decrease the environmental impact meanwhile increasing the cruising range. In this paper, the design of the Eco-SWAMP, a fuel cell powered autonomous surface vehicle, is presented starting from its battery-powered version, the SWAMP prototype. The experimental power consumption profile of the SWAMP during four missions is analysed to define the primary energy sources ratings of the Eco-SWAMP. After a commercial choice of primary sources, power management algorithms are designed and compared in MATLAB/Simulink environment by simulation results. The proposed procedure can be easily applied to any autonomous marine vehicle. Highlights: Autonomous vehicles are programmed or remotely controlled to follow a trajectory. The battery-powered SWAMP prototype is presented by experimental results. The fuel cell powered Eco-SWAMP is designed based on the power consumption profile. Simulation results in MATLAB/Simulink environment are presented. Four hours of single fill up cruising range are gained by the proposed procedure.